Effectiveness of Simulation Based Education on Competencies on Helping Babies Breathe and Perceived Self-Efficacy among Undergraduate Nursing Students, Kathmandu - Dangol, Bhuwan Kumari; Bista, Archana Pandey; Thapa, Muna Rana; Panta, Ganga; Darshandhari, Gayetri; Mukhia, Suzanna (Journal of Nursing and Health Sciences Nepal, 2023)
Introduction: Simulation based education is an intervention that enable students to become competent in performing clinical skills. The study aimed to find out the effectiveness of simulation-based education on competencies on performing Helping Babies Breathe (HBB)and perceived self-efficacy on performing Helping Babies Breathe among nursing students.Methods: Pre-experimental study design was adopted. Total 40 nursing students of BSc third year were included. Initially, pre-intervention data was obtained and simulation-based intervention on skills practice on Helping Babies Breathe was intervene by research team members based on HBB guideline and post-intervention data was obtained after 4 weeks of intervention. Data were analysed by using descriptive and inferential statistics specifically, paired t-test and Wilcoxon test was usedResults: All most all participants were able to initiate effective ventilation within a minute in post-test. The skills scores on performing all the steps of effective ventilation in post-test were increased. Specifically, there is a significant increased on skills score on initial steps of HBB after intervention with (p=0.001), birth time to initiation of effective ventilation (p= 0.002), continuing effective ventilation (p=0.005) and on overall skill competencies for performing HBB per minute (p=0.000). Regarding their perceived self-efficacy on performing HBB, score was higher on all aspects after intervention.Conclusions: Statistical significant increased scores on skills on performing Helping Babies Breathe (HBB)on post-test than pre-test signifies that simulation based education on HBB is effective on increasing skills competencies among nursing students and enhancing their perceived self-efficacy. Thus, skills practice on HBB is recommended to promote among nursing students in simulated labs.